Budi Daya Tanaman Oyong (Luffa acutangula L.) dan Terung (Solanum melongena L.) Berbasis Tumpangsari sebagai Upaya Peningkatan Produksi di Desa Neglasari - Rahmatun Nisful Maghfiroh; Prayoga Suryadarma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Most farmers in Neglasari cultivate annual crops as their livelihood. Vegetable commodities which are the main products of agriculture in Neglasari Village are oyong and eggplant. There are several cropping systems that are applied to these vegetable plants, two of which are monoculture and polyculture systems, especially the intercropping system. This report aims to determine the effectiveness of intercropping methods in the cultivation of oyong (Luffa acutangula L.) and eggplant (Solanum melongena L.) to increase production in Neglasari. The method used in this activity is the interview method and literature review. Interviews were conducted directly with several farmers in Neglasari as resource persons. Information on interview results is strengthened by conducting a literature review of sources relevant to the topic of discussion. The intercropping system has several advantages not possessed by monoculture systems. Tumpangsari is considered appropriate and effective in eggplant and oyong cultivation because farmers in Neglasari can earn more income than monoculture. In addition to increasing land productivity, this system can create biological stability so that it can suppress pests and diseases attacks and maintain the sustainability of land resources in this case soil fertility. Keywords: cultivation, eggplant, intercropping, oyong, production